(untitled) (Bangladesh Medical Journal, 2025)
Sub-fertility is an upsetting situation for childless couples who are experiencing a lot of physical, mental, social, and economic trauma. Many women go to an infertility clinic or gynecologist without their husbands because it is still considered a female issue, but male factors play a significant role in its etiology. Semen analysis is the most fundamental, useful and inexpensive means of assessing male factor infertility. This descriptive cross-sectional study was directed among sub-fertile males of infertile couples visiting the CARE (Centre for Assisted Reproduction) in Department of Obstetrics and Gynaecology of BIRDEM, Dhaka. The study was conducted among 126 males who were sub-fertile and aimed to evaluate the patterns of sperm parameters using semen analysis. After receiving informed consent and meeting eligibility criteria, participants were interviewed and semen analysis reports were obtained. Semen from the male partners were analyzed in the laboratory using the World Health Organization (WHO) 2021 criteria for human semen characteristics. Data were analyzed by using SPSS- 22. A total of 126 participants’ semen analysis and background characteristics were evaluated by using WHO standard for semen normality criteria, 2021. The WHO standard for semen normality criteria, 2021 was used to evaluate the semen analysis and background characteristics of 126 participants. The mean age (Mean±SD) of the study subjects was 34.92±6 years with their age range 21 – 52 years; among these respondents most of them (84.10%) were in the most productive fertile age group 21-40 years. In this study primary sub-fertility was observed in 68.3% of men and maximum of them (43.7%) were demanding to conceive over 3-5 years. Study found the following normal parameters of semen analysis; those are, 4.76% of the men had <1.4 ml semen volume per ejaculation, nearly one-fourth (22.22%) of men had sperm concentration <16 million/ml, more than half (55.56%) of the men’s total sperm motility was <42% and 17.46% of them were found abnormal morphology of sperm (teratospermia). The mean (Mean±SD) of semen volume was 2.59±0.99 ml, pH was 7.27±0.69, sperm concentration was 59.38±52.34 million/ml and the mean of total motility of the sperm was 36.70±24.71%; however mean of immotile sperm was 51.99±28.04% and normal morphology of sperm was 35.52±24.49%. An abnormal patterns of semen parameters were seen in majority (58.73%) of men; among them more than one-third (34.9%) of them were asthenozoospermia, 11.1% was azoospermia, Oligoasthenoteratozoospermia was 7.1%, Oligospermia 8% and Oligoasthenozoospermia 4.8%. According to age-wise distribution maximum cases of asthenospermia (20.6%) were observed between the age group of 31-40 years. Single-factor abnormalities was observed in 47.6% cases and 11.11% had combined factor abnormalities. This study found that asthenozoospermia was the main single factor abnormality or sub-fertile state, followed by azoospermia. Male partners of sub-fertile couples attending infertility clinics consistently have abnormal semen parameters, which are prevalent with primary sub-fertility. This study similarly found that asthenozoospermia and azoospermia were common abnormalities in male partners. Bangladesh Med J. 2024 Jan; 53(1): 18-25